Die Schenkung unter Auflage im römischen Recht - Kleňová, Veronika (2023)
The book presents a coherent theory of the law of donatio sub modo in its diachronic sequence and brings new results for the understanding of unjustified-enrichment-thinking, especially in the form of the condictio ob rem with a view to a general theory of dationes ob rem.